Cilovaja podgotovka sportsmenov, specializirujushhihsja v sportivnoj bor'be: sostojanie i perspektivy sovershenstvovanija - Manolaki, V. (Science in Olympic Sport, 2019)
The article analyzes the body of knowledge related to strength capacities and strength fitness of wrestlers as the most important components of their sportsmanship, which are of key importance for effective competitive activity. However, in special literature, this area of knowledge has not been adequately refl ected and is in clear discrepancy with the achievements of the general theory of sports training and the ideas that have developed in sports physiology, morphology, and biochemistry. The overwhelming amount of knowledge and practice relates to sports techniques and tactics. Issues related to other aspects of training, in particular, physical and such crucial for wrestling qualities as strength, are addressed extremely superficially and fragmentary, at a level incompatible with the one on which materials relating to technique and tactics are presented. The reasons for such a state are analyzed and the prospects for developing the problem of strength training of athletes specializing in wrestling are determined. The necessity of bringing knowledge in the fi eld of strength training of wrestlers into line with the types of muscular activity peculiar for technical and tactical actions, with the understanding that strength training of wrestlers should go by improving neuroregulatory components, and not by developing muscle hypertrophy has been demonstrated. The necessity of bringing the process of wrestlers` strength training in line with the characteristics of competitive activity and its energy supply, with the specifics of motor actions, individual characteristics of athletes, and the chosen style of conducting a bout, has been noted.